Allopatric divergence and secondary contact without genetic admixture for Arichanna perimelaina (Lepidoptera: Geometridae), an alpine moth endemic to the Hengduan Mountains. (12th May 2017) - LI, XINXIN; JIANG, NAN; CHENG, RUI; XUE, DAYONG; QU, YANHUA; HAN, HONGXIANG
Abstract: Mountain systems, especially at high altitudes, are an excellent model for determining the mechanisms underlying high species diversity and endemism. Herein, we elucidate the evolutionary history of the alpine moth Arichanna perimelaina (Wehrli), which is endemic to the Hengduan Mountains (HM) region in southwest China, based on three mitochondrial genes and two nuclear genes. Our results revealed six deeply divergent clades that corresponded to populations in different mountain systems in the HM region. Bayesian divergence time estimations suggested a mid‐ to late Pleistocene genetic divergence. The results also showed that the Mt Yulong (YL) region was a refugium and valley corridors established by glaciation during the Pleistocene allowed populations on the separate mountains to migrate. The reproductive isolation among the different clades on contact zone in the YL region may be associated with the asynchronous mating rhythms and/or the divergent mate recognition caused by the ecological source of divergent selection. Allopatric divergence associated with complex topographies and climatic oscillations, regional dispersal via valley corridors and the suitable refugium of the YL region shaped the genetic divergence and distribution pattern of A. perimelaina in the HM region. These findings highlight the essential role of complex terrain and climatic fluctuations in shaping the unique phylogeographic history of a narrow alpine moth, and provide insights into the mechanisms underlying high species richness and endemism in the HM region. Abstract : There is strong genetic differentiation for an alpine moth Arichanna perimelaina across the Hengduan Mountains region. The YL region is a contact zone of genetically divergent populations caused by regional dispersal via valley corridors and the suitable refugium during glacial periods. The reproductive isolation among the divergent populations may be associated with the asynchronous mating rhythms and/or the divergent mate recognition caused by the ecological source of divergent selection.